Effect Of Homogenate From Different Oyster Species On Perkinsus Marinus Proliferation And Subtilisin Gene Transcription - Brown, GD; Kaattari, SL; Reece, Kimberly S (W&M ScholarWorks, 2005)
The modulation of Perkinsus marinus proliferation and subtilisin gene transcription by host (oyster) tissue was examined. Perkinsus rnarinus cells were cultured for 4 weeks in media supplemented with extract from either one of four different Crassostrea virginica stocks or with extract from one of two other Crassostrea species, C. ariakensis and C. gigas. After 4 weeks in culture, we determined cell counts and relative subtilisin gene transcription levels using quantitative real-time polymerise chain reaction (qRTPCR). Cell proliferation and subtilisin gene transcription were significantly lower when P. marinus' cells were grown in the presence of homogenate from any of the three oyster species than in unsupplemented media. Perkinstrs marinas subtilisin gene transcription was also significantly lower in cells cultured in media supplemented with homogenate from either C. ariakensis or C. gigas, than in media containing extract from the native oyster host, C. virginica. Gene transcription levels among cells grown in media supplemented with homogenate from the different stocks of C. virginica were not significantly different from one another.